UTILIZING VARIOUS MEDIA IN TEACHING ENGLISH TO YOUNG LEARNERS: IS IT MEANINGFUL? - Sri Wahyuningsih; ELvira Sho'idatut Taqiyah (Universitas 17 Agustus 1945 Semarang, 2022)
Recently, English has been used as a language of communication. This demand makes parents compete to send their children to schools that use English as the medium of language in learning. Learning English as a foreign language in Indonesia has also begun to reach the primary school level. The present study elaborates on the importance of utilizing interesting media to teach English to young learners. A descriptive qualitative method was adopted in this study. Data were collected through interviews with two teachers at Indonesian elementary schools. The findings reveal that in learning English, appropriate learning methods and interesting media are needed to increase students' interest and desire to use English in fun and interesting learning activities for students, both spoken and written fluently and in accordance with their social context.